(untitled) (Agroindustrial Science, 2025)
The objective of this study was to evaluate the effect of foliar fertilization with alternative zinc (Zn) sources on the nutritional status and growth of young ´Valencia´ orange (Citrus sinensis L. Osbeck) trees grown in calcareous soil (pH = 8.1). Nine treatments were tested: the commercial amino chelates Aton Zn (0.3% and 0.5%) and Kelatex Zn Forte (0.5% and 1.0%); the commercial Zn microparticles Basfoliar Zn 75 Flo (0.1% and 0.2%); ZnSO4H2O (0.3% and 0.5%); and a control treatment with no Zn application. The Zn concentration in leaves increased with the application of Aton Zn (0.3%), Kelatex Zn Forte (0.5% and 1.0%), and ZnSO4H2O (0.3% and 0.5%). The Zn concentration in roots increased only in trees sprayed with Kelatex Zn Forte (1.0%). The chlorophyll index (SPAD readings) decreased in most treatments, except in leaves sprayed with ZnSO4H2O (0.3%) and Kelatex Zn Forte (1.0%). The N concentration in leaves increased with the application of ZnSO4H2O (0.5%), while P levels did not increase in any treatment. The foliar K concentration increased in trees sprayed with Aton Zn (0.3% and 0.5%), Basfoliar Zn 75 Flo (0.1%) and ZnSO4H2O (0.3%). The concentrations of Mn, Cu, and B in leaves remained unchanged across all treatments. Foliar Fe concentration increased in trees sprayed with Kelatex Zn Forte (0.5%) and ZnSO4H2O (0.3%). Zn application had no significant effect on tree growth. The amino chelate Kelatex Zn Forte at a 1.0% dose shows promising potential by increasing Zn concentrations in leaves and roots while maintaining the chlorophyll index.